Gerastenian yhteys aktiivisena vanhenemiseen - Nummi, Emilia (2025)
Nummi, E. 2025. The relationship between frailty and active ageing. Faculty of Sport and Health Sciences, University of Jyväskylä, Gerontology and Public Health, Master’s thesis, 58 pp.